Histological Study of Phyllidia coelestis (Nudibranch) Epidermal Tissue from Pasir Putih, Situbondo - Karunia Galih Permadani; Bambang Retnoaji (Indonesian Journal of Biology Education, 2018)
Nudibranch are a mollusk which can be found in all zones of ocean. Further, they are distributed widely from subtropical to tropical areas. The Nudibranch is characterized by lack of a shell and usually have a bright shiny color. Nudibranch has a potency to be used in the medical field because they have chemical compound inside their body. These chemical compound are the result of secondary metabolites from symbiosis with zooxanthellae in nudibranch tissues.  This research aims to study the structure of epidermal tissue of the Phyllidia coelestis collected from Pasir Putih, Situbondo, East Java Indonesia. The results showed that the epithelial structure of the Phyllidia coelestis composed of cuboidal epithelium with vacuoles spread regularly along the mantle layer below the epidermal layer. Gland cells are rarely found in the outer epithelial layer. The foot epidermal layer consisted of simple ciliated columnar epithelial cells, with goblet-shaped mucous secreting glands among the epithelium. Gill tissue structure was composed of cell layers of cuboidal ciliated epithelial cells resting on a basement membrane and connective tissues